Extending educational metadata schemas to describe adaptive learning resources - CONLAN, OWEN; WADE, VINCENT PATRICK (ACM, 2001)
This paper describes a generic technique for representing Adaptive Learning Resources by extending current metadata schemas. The requirement for the work described here has grown out of the necessity to facilitate accurate discovery and integration of Adaptive Learning Resources, namely Adaptive Hypermedia Services.
PUBLISHED
Keywords: Adaptive Hypermedia Services, Adaptivity